Remembering Rebellion, Remembering Resistance: Collective Memory, Identity, and the Veterans of 1869-70 and 1885 - McRae, Matthew J (Scholarship@Western, 2018)
This dissertation analyses two of the Canadian state’s earliest military operations through the lens of personal and collective memory: The Red River conflict of 1869-70 and the Northwest Campaign of 1885. Both campaigns were directed by the Canadian state against primarily Métis and First Nations opponents. In each case, resistance to Canadian hegemony was centered on, though not exclusively led by, Métis leader Louis Riel. This project focuses on the various veteran communities that were created in the aftermath of these two events. On one side, there were the Canadian government soldiers who had served in the campaigns and were initially celebrated by English-Canadian society. On the other side, there were Métis and First Nations warriors who had resisted the state. They were largely forgotten by the English-Canadian public, but still respected and commemorated within their own communities. This dynamic changed in the latter part of the twentieth century. After the last Canadian militia veterans passed away in the 1950s, they quickly faded from English-Canadian collective memory. At the same time, calls from Métis and First Nations peoples for greater recognition of their veterans began to receive more attention. By the end of the twentieth century, the narrative of the Canadian militia veterans had all but disappeared, but was not replaced in English Canada with a narrative of Indigenous veterans. The efforts of these veteran communities to promote particular visions of the past speaks to questions of national identity that still persist today.